The Jewishness of Israelis : responses to the Guttman report - Liebman, Charles S.; Katz, Elihu, 1926-2021 (Albany : State University of New York Press, 1997)
Annotation Analyzes a recent report on a survey of the religious beliefs and behavior of Israeli Jews, and the intense public debate that it produced. In December 1993, the Louis Guttman Israel Institute of Applied Social Research released the results of the most comprehensive study ever undertaken of the religious beliefs and behavior of Israeli Jews. The study revealed that Israeli Jews were far more traditional in their religious beliefs and behavior than previously thought, resulting in an intense public debate within Israeli society. This book summarizes the Guttman Report and describes how the media and Israeli intellectuals responded to it and imposed their own interpretations. It then analyzes the report in greater detail and puts in global perspective Israeli Jews' ritual behavior, religious beliefs, and attitudes toward religion in public life. The editors conclude that the religious traditionalism of Israeli Jews is unique among advanced industrial societies. They seek to explain this uniqueness in terms of the particular nature of Israeli society, focusing on Israel's security problems and suggesting the impact that a new securit.
Beliefs, observances and social interaction among Israeli Jews : the Guttman Institute Report / Shlomit Levy, Hanna Levinsohn, and Elihu Katz -- The media and the Guttman Report / Charles S. Leibman -- Academics and other intellectuals / Charles S. Liebman -- Behavioral and phenomenological Jewishness / Elihu Katz -- Religion and modernity : the special case of Israel / Charles S. Liebman -- Cultural conflict in Israeli society / Charles S. Liebman -- Appendix : The Van Leer Papers.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Jews -- Israel -- Public opinion; Orthodox Judaism -- Israel -- Public opinion; Israelis -- Religious life; Public opinion -- Israel; Social surveys -- Israel; Juifs -- Israël -- Opinion publique; Judaïsme orthodoxe -- Israël -- Opinion publique; Israéliens -- Vie religieuse; Opinion publique -- Israël.; Enquêtes sociales -- Israël.; RELIGION -- Judaism -- History; Israelis -- Religious life; Jews -- Public opinion; Orthodox Judaism -- Public opinion; Public opinion; Social surveys; Israel